Optical modeling of atmospheric black carbon aerosol ensembles with complex particle morphology - Yu Wu; Lijuan Zheng; Yuhan Wu; Zeyu Wang; Yanming Guo (Environmental Research Letters, 2024)
Black carbon (BC) aerosol is one of the most important factor in global warming. BC radiative forcing remains unconstrained, mainly because of the uncertain parameterizations of its absorption and scattering properties in the atmosphere. The single sphere model is widely used in current climate assessment of BC aerosols due to its computational convenience, however, their complex morphologies in particle level are excessively simplified which leads to computed inaccuracy. In this study, we present a dynamic model for optical calculations of BC aerosol ensembles considering their complex fractal aggregate morphologies with the constraint of max monomer numbers ( N _s, max ) and radius ( a _max ). We show that the simulation accuracy of the dynamic model with suitable values of N _s, max and a _max may achieve ∼95% while the computation time may reduce to ∼6%. We find that optical properties of BC aerosol ensembles can be simulated for higher accuracy or faster calculation by performing different selections of monomer numbers and radius in their size distributions. This method enables extensive and accurate optical calculations of BC particles with complex morphologies, which would be useful for the remote sensing inversion and the assessment of climate.